SPECIFICITY OF CONTROL AND EVALUATION ACTIVITY IN TRAINING OF FUTURE SOCIAL WORKERS: сontrol and evaluation activities; student achievement; project activity; work in mini-groups; self-evaluation and mutual evaluation; level of internality; professional competence; Social Worker - Radchenko, Maryna; Prozhoha, Iryna (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The purpose of the article: the article is devoted to highlighting the problem of finding effective methods of monitoring and evaluating the academic achievements of students - future social workers. It is noted that in the conditions of crisis phenomena experiencing the whole world, social work and training of a social worker in higher educational institutions become especially important. The necessity of choosing such means of control and evaluation activities of students' academic achievements that meet the needs and specifics of the future specialty is substantiated. The experience of evaluation, self-evaluation and mutual evaluation of the results of project activity of students of specialty 231 "Social work" FLSK NAU is analyzed. A brief overview of scientific works devoted to solving the issues of the theoretical basis of social work is offered, the components of professional competence of social workers are given. Research methods: theoretical general scientific methods of generalization, formalization and abstraction were used, as well as the longitudinal method of organizing the research, which was conducted in the first semesters of 2019/20 and 2020/21 academic years. Among the empirical methods of obtaining scientific data, observational (observation) and diagnostic scale methods in the form of questionnaires and surveys were used. In the process of processing the research results, both standard methods of statistical data processing (quantitative processing) and methods of qualitative analysis were selected. Results:methods of control and evaluation of educational achievements of students - future social workers in the process of preparation and presentation of projects, namely: self-evaluation and mutual evaluation are analyzed. As a result of empirical research it is established that the system of complex mutual evaluation presented in the article helps to increase the level of student success and increases the number of attendance classes by creating additional positive incentives and internal cognitive motives for future social workers. An example of a method of assessing group work of students used in the real educational process is given. The advantages of group project activities in the context of training future social workers are emphasized. Conclusions: the increase of the level of responsibility (internality) of students for the results of their own activity in the process of using the methods of self-evaluation and mutual evaluation in the evaluation of educational projects is determined. The effectiveness of work in mini-groups as a powerful factor in optimizing the socio-psychological competence of students as subjects of communication is proved. The need to take into account in the process of control and evaluation activities the specifics of future professional activities of a social worker.The direction of further scientific researches is outlined